The Contribution of Motor Educability to Basic Taekwondo Techniques - Nirwasita, Reynard Abner; Rusdiana, Agus; Imanudin, Iman (STKIP Pasundan, 2025)
This study aims to analyze the relationship between motor educability and mastery of basic Taekwondo techniques among young athletes at Mutiara Lid's Club (MLC). Using a quantitative descriptive correlational method with a cross-sectional approach, the study involved 35 athletes as respondents. Data were collected through motor educability and basic Taekwondo technique tests. Pearson correlation analysis showed a correlation value (r) of -0.100 with a significance value (p) of 0.569, indicating a very weak and non-significant relationship between the two variables. Simple linear regression analysis also showed that motor educability contributed only 1% to basic technique mastery, with the same non-significant p-value (0.569). Therefore, no significant relationship was found between motor educability and basic technique performance. Other factors such as training experience, motivation, or coaching methods may have a greater influence. Further research is recommended with a larger sample size and additional variables to obtain more comprehensive results.